Lingkungan Kampus dan Kemampuan Komunikasi Berbahasa Arab Mahasiswa - Azizah, Mufidah Asri; Setiyawan, Agung; Marcella, Azmalia Anastasya; Limbong, Ahya Dita Satiarmia; Cania, Fitri Nurhasana (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
The purpose of this study is to describe how the campus environment shapes students’ Arabic communication skills. This study applies a descriptive qualitative approach with a field study conducted at the Arabic Language Education Study Program, Faculty of Tarbiyah, UIN Imam Bonjol Padang. Data collection was conducted through participatory observation, in-depth interviews, and documentation, and the data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data presentation, and conclusion drawing, with data validity reinforced through source and method triangulation. The results showed that a campus environment that actively encourages the use of Arabic significantly improves students’ communicative skills, particularly fluency, confidence, and the courage to express opinions. Social interaction among students and support from lecturers and the academic community also strengthen functional and contextual language practice. However, this study also identified several obstacles, including inconsistent use of Arabic outside the classroom, limited space for continuous practice, and psychological factors among students. Therefore, it is necessary to strengthen language policies and develop a campus ecosystem that consistently supports the use of Arabic to optimally and sustainably improve students’ communicative competence.